KELUARGA DAN POLA PENGASUHAN ANAK - Rohmat Rohmat (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
The family is the dominant aspect of a significant contribution to the formation of characters that includes a child’spersonality, intellectual and spiritual intelligence. Understanding of the basic functions of family and parenting becomes important torecognize and implemented. The basic functions of the family include: reproduction, socialization, the assignment of social roles, economicsupport. While parenting can be done in several ways through: the style of parents in child care, effective communication with children,helping solve problems faced by children, making effective punishment and reward become more effective methods